Singing me into this land: the territorialization of a spiritual ecosystem - MacDonald, Michael B. (My University, 2009)
The fear of environmental catastrophe is very real in our daily lives. Dealing with fear at times means combating it. A small pagan community in Washington State gathers together up to eight times a year to ritualize their connection to nature. These rituals use music as a magic to transform the consciousness of the participants. Becoming one with nature in a spiritual-ecosystem allows the forces of nature to become animate and real. This is the magic of music.
Keywords: fear; music; paganism; spiritual-ecosystem